Los saberes en la medicina intercultural de la Unión Campesina del Azuay (Ecuador): construcción territorial y colectiva de aprendizajes transformadores - Tubay Zambrano, Fanny (2024)
The study shows how healers from the Peasant Union of Azuay (UNASAY-E) in Ecuador, faced with the needs of today's world, raise the need to continue training; and they make known their vision of what knowledge they require to care for the body, mind and spirit. The research is ethnographic and uses tools such as semi-structured interviews and focus groups. The results reveal that the knowledge inherited from generation to generation is in permanent territorial and collective construction. It also explains which resources, natural medicines and treatments are applied for healing. The investigation concludes that ancestral medicine continues to be devalued and folklorized, even though, on the one hand, it is recognized in the national Constitution and, on the other, it confers well-being to the social structure.